PENERAPAN STRATEGI PEMBELAJARAN THE FIRING LINE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMA NEGERI 1 KUBU ROHIL - Yanti, Yuli; ', Erviyenni; ', Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research aims to improve the student learning achievement on the subject Atomic Structure and System of Periodic unsure in class XI Science Senior High School 1 Kubu Rohil. This type of research is experimental research study design randomized control group pretest-posttest. Research conducted at Senior High School 1 Kubu Rohil. Samples of the research were students of class XI Science 1 as an experimental class and class XI Science 2 as the control class. Experimental class is a class that is applied learning strategy the firing line whereas the untreated control class. Data analysis technique used was t test. Based on test data analysis obtained tcount>ttable is 2,29>1,67, meaning that the use of learning strategy the firing line can increase student achievement on the subject of structure of atoms and periodic system of elements in class XI Science Senior High School 1 Kubu Rohil by category increase achievement (N-Gain) high at 0.72.Keywords : Learning Achievement, Learning Strategy The Firing Line, and Atomic Structure and System of Periodic unsure